Ribotyping and virulence markers of Yersinia pseudotuberculosis strains isolated from animals in Brazil - Carlos Henrique Gomes Martins; Taís Maria Bauab; Clarice Queico Fujimura Leite; Deise Pasetto Falcão (Memorias do Instituto Oswaldo Cruz, 2007)
Ribotyping and virulence markers has been used to investigate 68 Yersinia pseudotuberculosis strains of serogroups O:1a and O:3. The strains were isolated from clinical material obtained from healthy and sick animals in the Southern region of Brazil. Ribotypes were identified by double digestion of extracted DNA with the restriction endonucleases SmaI and PstI, separation by electrophoresis and hybridization with a digoxigenin-labeled cDNA probe. The presence of the chromosomal virulence marker genes inv, irp1, irp2, psn, ybtE, ybtP-ybtQ, and ybtX-ybtS, of the IS100 insertion sequence, and of the plasmid gene lcrF was detected by polymerase chain reaction. The strains were grouped into four distinct ribotypes, all of them comprising several strains. Ribotypes 1 and 4 presented distinct profiles, with 57.3% genetic similarity, ribotypes 2 and 3 presented 52.5% genetic similarity, and genetic similarity was 45% between these two groups (1/4 and 2/3). All strains possessed the inv, irp1, and irp2 genes. Additionally, strains of serogroup O:1a carried psn, ybtE, ybtP-ybtQ, ybtX-ybtS, and IS100. As expected lcrF was only detected in strains harboring the virulence plasmid. These data demonstrate the presence of Y. pseudotuberculosis strains harboring genotypic virulence markers in the livestock from Southern Brazil and that the dissemination of these bacteria may occur between herds.